2014
DOI: 10.3390/nu6020605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beetroot Juice Supplementation on Aerobic Response during Swimming

Abstract: The beneficial effects of beetroot juice supplementation (BJS) have been tested during cycling, walking, and running. The purpose of the present study was to investigate whether BJS can also improve performance in swimmers. Fourteen moderately trained male master swimmers were recruited and underwent two incremental swimming tests randomly assigned in a pool during which workload, oxygen uptake (VO2), carbon dioxide production (VCO2), pulmonary ventilation (VE), and aerobic energy cost (AEC) of swimming were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
2
47
0
3
Order By: Relevance
“…Conversely, the effects of nitrate supplementation on swimming performance -4 a sport where, anecdotally, nitrate supplementation appears to be highly prevalent -are poorly understood. Recently, Pinna et al (2014) reported an increased workload at the anaerobic threshold and reduced aerobic energy cost during incremental tethered swimming consequent to nitrate supplementation. These results suggest a potentially beneficial effect of nitrate supplementation during swimming.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the effects of nitrate supplementation on swimming performance -4 a sport where, anecdotally, nitrate supplementation appears to be highly prevalent -are poorly understood. Recently, Pinna et al (2014) reported an increased workload at the anaerobic threshold and reduced aerobic energy cost during incremental tethered swimming consequent to nitrate supplementation. These results suggest a potentially beneficial effect of nitrate supplementation during swimming.…”
Section: Introductionmentioning
confidence: 99%
“…Así, el jugo de betarraga podría tener impacto positivo en las respuestas fisiológicas al ejercicio. En el músculo esquelético, el jugo de betarraga estimula la producción de NO, que a su vez aumenta el flujo sanguíneo y mejora la disposición del O2 muscular mientras se camina, corre, monta bicicleta o nada (3) . También el nitrato de la espinaca, betarraga, lechuga y otros vegetales ricos en nitratos, aumenta la eficiencia de mitocondrias humanas aisladas, lo que se refleja en disminución en la tasa metabólica en reposo y la formación de especies reactivas de oxígeno, efecto que podría tener implicancias en la regulación de la función metabólica en la salud y la enfermedad (4) .…”
Section: Editorialunclassified
“…Dietary nitrate supplementation in the form of beetroot juice (BR), as a precursor to NO, has acquired much attention for its proposed ergogenic properties and improves performance in sports such as rowing (2) and swimming (3) . Considering that most studies of BR ingestion to date have used endurance-related exercise models, there is a clear gap in literature regarding the effects of acute ingestion of BR on repeated sprint performance (RSP) as representative of team sport performance.…”
mentioning
confidence: 99%